ASSESSMENT OF SOIL POLLUTION IN AKTOBE REGION BY HEAVY METALS BASED ON GIS TECHNOLOGIES (Journal of Geography and Environmental Management, 2025)
In this study, the level of soil contamination with heavy metals in the Aktobe region was studied using cartographic methods. The study analyzed the spatial distribution of chromium (Cr), nickel (Ni), arsenic (As), molybdenum (Mo), cobalt (Co), zinc (Zn), lead (Pb), copper (Cu), cadmium (Cd) and boron (B) in the soil.. Based on the data obtained on the basis of the geographic information system (GIS), information and assessment maps have been developed.The main purpose of the study is to assess the impact of industrial enterprises in the region on soil pollution with heavy metals. For this purpose, soil samples were taken and laboratory analysis was carried out in areas close to the Don Mining and Processing Plant, mining enterprises of the Mogajar district, Aktobe Ferroalloy Plant, as well as oil and gas fields in the region. The data obtained was processed using the Inverse Distance Weighted (IDW) interpolation method.The results of the study revealed highly concentrated areas of heavy metals in the region. It has been established that in regions where the influence of oil and gas producing and mining plants is observed, there are high concentrations of the elements lead (Pb), cadmium (Cd) and zinc (Zn). In addition, a comprehensive cartographic model has been developed that describes the patterns of spatial distribution of individual elements.The results obtained stat.gov.kz They were compared with official statistical data, and the features of industrial pollution zones were analyzed. During the study, there was a discrepancy between the concentrations of heavy metals in areas close to production facilities and official data, which indicates the need to improve the regional monitoring system
Keywords: GIS technologies; geospatial analysis; soil contamination with heavy metals; interpolation; spectrometry